2016
DOI: 10.1590/s0100-204x2016001000005
|View full text |Cite
|
Sign up to set email alerts
|

Seleção simultânea em progênies de sorgo-sacarino por meio de índices de seleção

Abstract: Resumo -O objetivo deste trabalho foi comparar ganhos genéticos obtidos por diferentes índices de seleção aplicados a múltiplos caracteres agronômicos de sorgo-sacarino (Sorghum bicolor). Foram feitas avaliações de 189 progênies F5 e sete testemunhas, em delineamento de blocos incompletos, com três repetições. Mensuraram-se os caracteres produtividade de matéria verde, teor de sólidos solúveis totais, extração de caldo, teor de sacarose no caldo e sólidos solúveis totais por hectare. Analisaram-se os índices d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
1
3
1
Order By: Relevance
“…The absence of genetic variance for TSS might have occurred due to environmental fluctuations, especially rainfall during the harvest season (Figure 1), which may have led to the dilution of soluble solids of the stem juice. Unlike what was observed in this study, França et al (2016) observed high heritability estimates for TSS.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The absence of genetic variance for TSS might have occurred due to environmental fluctuations, especially rainfall during the harvest season (Figure 1), which may have led to the dilution of soluble solids of the stem juice. Unlike what was observed in this study, França et al (2016) observed high heritability estimates for TSS.…”
Section: Resultscontrasting
confidence: 99%
“…The sum of rank index was not promising because it showed the lowest estimated gain from selection for the trait GMP in the single-trait approach and PH, GMP, and TBH in the multi-trait analysis (Figure 2). Inefficiency in obtaining satisfactory gains in the sweet sorghum crop by the Mulamba and Mock index was also observed by França et al (2016) through the univariate mixed-model approach, since this index provided the lowest estimates of gains from selection for all traits measured by the authors, some of which were the same as those evaluated here (GMP and TBH).…”
Section: Msupporting
confidence: 64%
See 1 more Smart Citation
“…Characteristics that have a high heritability and high correlation with a quantitative characteristic are likely to be used in the indirect selection. Oliveira (2015) and França et al (2016) estimated H 2 values > 0.7 for soluble solids content in studies of genetic parameters in sorghum. Therefore, the measurement of soluble solids content may be considered of great importance for studies on biofuel yield, which can The total and direct effects exerted by culm yield presented values similar to those by soluble solids content, but of lesser magnitude, presenting 0.8516 for total effect and 0.5254 for direct effect on yield of theoretical ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy consists in establishing a new trait from a linear combination of all the target traits, considering that the weight coefficients are estimated to maximize the correlation between the index and the true genetic values of the genotypes to be selected. Several studies have addressed the application of selection indexes to plant breeding, leading to gains in a set of traits simultaneously (França et al 2016;Junqueira et al 2016;Kumar et al 2016;Silva et al 2016). Thus, the interest for studying the methodology efficiency in genomic selection has increased (Ceron-Rojas et al 2015;Covarrubias-Pazaran et al 2018;Fernandes et al 2018).…”
Section: Plant Breedingmentioning
confidence: 99%